2018
DOI: 10.24018/ejers.2018.3.5.746
|View full text |Cite
|
Sign up to set email alerts
|

Application of Firefly Optimization Technique for Solving Convex Economic Load Dispatch of Generation On Nigerian 330 kV, 24-Bus Grid System

Abstract: Abstract-Firefly optimization is a population based technique in which the attractiveness of a firefly is determined by its attractiveness which is then encoded as the objective function of the optimization problems. Firefly algorithm is one of the newest meta-heuristic algorithms based on the mating or flashing behavior of fireflies. Economic load dispatch of generation allocates power generation to match load demand at minimal possible cost without violating power units and system constraints. This paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The two equations had for each load bus given by Equation ( 5) and Equation (6), and one equation for each voltagecontrolled bus given by Equation (5). The terms ( ) and ( ) are the difference between the scheduled and calculated values known as the power residuals, given by:…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The two equations had for each load bus given by Equation ( 5) and Equation (6), and one equation for each voltagecontrolled bus given by Equation (5). The terms ( ) and ( ) are the difference between the scheduled and calculated values known as the power residuals, given by:…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Table (5) shows the values of voltage magnitude, Active Power, Reactive Power Generation, Active and Reactive Load at each bus from the application of the Newton-Raphson method. Table (6) shows the values of the production cost, the active and reactive power loss when applying 4.2.2 Genetic Algorithm Optimization Applications: Table (7) shows the values of voltage magnitude, active power, reactive power generation, active and reactive load at each bus from the applications of the Genetic Algorithm Optimization method, the Newton-Raphson method, on the 14-Bus system. Table (8) shows the cost values and the active and reactive losses.…”
Section: Case Amentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that PSO generated the lowest cost of generation and power loss when compared with other methods mentioned. Ajenikoko et al (2018) applied Firefly Optimization Technique (FFOT) to solve EDP of generation on Nigerian grid system. The EDP problem was expressed to minimize total fuel cost.…”
Section: Generation Dispatch Of Nigerian Power Systemmentioning
confidence: 99%